{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

Chemical Engineering Hand Written_Notes_Part_50

# Chemical Engineering Hand Written_Notes_Part_50 - 102 3...

This preview shows pages 1–2. Sign up to view the full content.

102 3. LINEAR ALGEBRAIC EQUATIONS AND RELATED NUMERICAL SCHEMES (6.36) x ( k +1) = x ( k ) + 4 x ( k ) Step x ( k +1) predicts a function change (6.37) F ( k ) = F ( k +1) F ( k ) We impose the following two conditions to obtain estimate of J ( k +1) . (1) In the direction perpendicular to 4 x ( k ) , our knowledge about F is maintained by new Jacobian estimate J ( k +1) . This means for a vector, say r , if [ x ( k ) ] T r = 0 , then (6.38) J ( k ) r = J ( k +1) r In other words, both J ( k ) and J ( k +1) will predict some change in direc- tion perpendicular to x ( k ) . (2) J ( k +1) predicts for 4 x ( k ) , the same F ( k ) in linear expansion, i.e., (6.39) F ( k +1) = F ( k ) J ( k +1) 4 x ( k ) or (6.40) J ( k +1) 4 x ( k ) = F ( k ) Now, for vector r perpendicular to 4 x ( k ) , we have (6.41) J ( k +1) r = J ( k ) r + y ( k ) [ z ( k ) ] T r As (6.42) J ( k +1) r = J ( k ) r We have (6.43) y ( k ) [ z ( k ) ] T r = 0 Since 4 x ( k ) is perpendicular to r , we can choose z ( k ) = 4 x ( k ) . Substituting this choice of z ( k ) in equation (6.34) and post multiplying equation (6.34) by 4 x ( k ) , we get (6.44) J ( k +1) 4 x ( k ) = J ( k ) 4 x ( k ) + y ( k ) [ 4 x ( k ) ] T 4 x ( k ) Using equation (3), we have (6.45) F ( k ) = J ( k ) 4 x ( k ) + y ( k ) [ 4 x ( k ) ] T 4 x ( k ) which yields (6.46) y ( k ) =

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}